Efektivitas Penegakan Pasal 287 Ayat (2) Undang-Undang Lalu Lintas dan Angkutan Jalan terhadap Pelanggaran APILL: Analisis Yuridis Normatif dalam Perspektif Sistem Hukum - Muhammad Zaidan Firdaus (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study examines the effectiveness of law enforcement regarding violations of Article 287 paragraph (2) of Law Number 22 of 2009 on Road Traffic and Transportation, particularly concerning red-light violations (APILL). Although the legal provisions are clearly formulated, practical implementation reveals a gap between the normative expectations (das Sollen) and actual conditions (das Sein). This research employs a normative juridical method supported by secondary empirical data, analyzed through Lawrence M. Friedman’s legal system theory and Satjipto Rahardjo’s theory of law enforcement. The findings show that the effectiveness of enforcing red-light regulations is influenced by structural aspects of law enforcement agencies, the community’s weak legal culture, and supporting facilities such as the uneven distribution of ETLE systems. The study concludes that the enforcement of Article 287 paragraph (2) remains suboptimal, and therefore requires strengthening ETLE infrastructure, improving officer professionalism, reassessing the proportionality of sanctions, and enhancing public legal education to increase traffic compliance.